Increasing the Strength, Hardness, and Survivability of Semiconducting Polymers by Crosslinking. Issue 3 (1st December 2022) - Chen, Alexander X.; Hilgar, Jeremy D.; Samoylov, Anton A.; Pazhankave, Silpa S.; Bunch, Jordan A.; Choudhary, Kartik; Esparza, Guillermo L.; Lim, Allison; Luo, Xuyi; Chen, Hu; Runser, Rory; McCulloch, Iain; et al.
Abstract: Crosslinking is a ubiquitous strategy in polymer engineering to increase the thermomechanical robustness of solid polymers but has been relatively unexplored in the context of π‐conjugated (semiconducting) polymers. Notwithstanding, mechanical stability is key to many envisioned applications of organic electronic devices. For example, the wide‐scale distribution of photovoltaic devices incorporating conjugated polymers may depend on integration with substrates subject to mechanical insult—for example, road surfaces, flooring tiles, and vehicle paint. Here, a four‐armed azide‐based crosslinker ("4Bx") is used to modify the mechanical properties of a library of semiconducting polymers. Three polymers used in bulk heterojunction solar cells (donors J51 and PTB7‐Th, and acceptor N2200) are selected for detailed investigation. In doing so, it is shown that low loadings of 4Bx can be used to increase the strength (up to 30%), toughness (up to 75%), hardness (up to 25%), and cohesion of crosslinked films. Likewise, crosslinked films show greater physical stability in comparison to non‐crosslinked counterparts (20% vs 90% volume lost after sonication). Finally, the locked‐in morphologies and increased mechanical robustness enable crosslinked solar cells to have greater survivability to four degradation tests: abrasion (using a sponge), direct exposure to chloroform, thermal aging, and accelerated degradation (heat, moisture, and oxygen). Abstract : Crosslinking is a common strategy in polymer engineering for tuning the mechanical properties of a solid polymer, yet seldom explored for semiconducting polymers. It is shown that a four‐armed azide crosslinker ("4Bx") can be used to increase the strength, hardness, and survivability of polymeric semiconductors for device applications requiring mechanical robustness.